ANTIDIABETIC POTENTIAL OF XANTHOSOMA BRASILIENSE AND JACQUEMONTIA PENTANTHOS: A COMPARATIVE STUDY - PARVATHY CHANDRAN (The Journal of Research ANGRAU, 2025)
Diabetes mellitus represents a long-term metabolic disorder that demands effective control strategies. This comparative investigation explored the antidiabetic potential of extracts from Xanthosoma brasiliense and Jacquemontia pentanthos. The study was conducted during 2024. The extracts were evaluated for their inhibitory activities against alpha-amylase and alpha glucosidase enzymes. The results showed that Xanthosoma brasiliense exhibited potent inhibitory activities against alpha-amylase (IC50 : 3.741924 ± 0.011 2.39175 ± 0.021 g/mL) and alpha-glucosidase (IC50 : g/mL). Jacquemontia pentanthos demonstrated significant inhibitory activities against alpha-glucosidase (IC50 : 3.368435 ± 0.031 g/mL) and moderate activity against alpha amylase (IC50 : 15.38087 ± 0.027 g/mL). The results indicate that extracts of Xanthosoma brasiliense and Jacquemontia pentanthos could aid in creating natural antidiabetic agents, offering an alternative or supportive option for diabetes management.